La politique israélienne de Sadate ou l’énigme de la stratégie égyptienne - Hentsch, Thierry (Études internationales, 1980)
It is generally accepted that a power relation is at the base of every negotiation and that, to the extent possible, each State attempts to negotiate when that relation is the most weighted in its favour, especially if the subject matter of negotiation is perceived by it as being of vital importance.Over several years all of Israel's neighbours, Egypt among them, obstinately refused to negotiate (at least openly) with the Zionist State apparently counting on an improvement in the power relation in their favour. An improvement moreover that eventually seemed possible with the relative yet nonetheless important successes of the October 1973 war.The enigma that Sadat's policy constitutes from this vantage point resides precisely in the fact that that policy appears to upset the power relation that made the October War possible and that led to Israel's first setback. The economic difficulties and reorientation of the Egyptian regime (both towards the West and towards private enterprise) do not, by themselves, explain what is referred to as Egypt’s « defeatist » diplomacy. This diplomacy also reflects a strategic coherency that can only be understood within the historical perspective of the Arab-Israeli conflict and by undertaking a rigourous analysis of Zionism and its principal sources of political support. Sadat, by a paradoxical exploitation of a position of weakness, attempts to transform politically that relative weakness into a position of strength in order to wrest from Israel that which the Arabs have not succeeded in obtaining by armed force. He pursues the war, but by the other means. Nevertheless, the success of these means depends to a great extent on the attitudes of the other countries of the battlefield.